2001
DOI: 10.1046/j.1365-2893.2001.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of hepatitis A and hepatitis E in urban and rural India (1982–98)

Abstract: The epidemiology of hepatitis A virus (HAV) and hepatitis E virus (HEV) was assessed among age-stratified urban high socioeconomic, lower middle socioeconomic status and rural populations from western India in 1998. When compared with previous surveys, a clear shift from high to intermediate endemicity of HAV was evident only for higher socioeconomic population (1982-98), raising the possibility of outbreaks of hepatitis A in this category. A decrease in anti-HAV positivity was noted in rural children aged 6-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…The present study showed that one third of hepatitis A patients had insufficient sanitation or poor hygienic conditions with overcrowded population. As reported earlier, low standards of sanitation promote transmission of the virus, therefore, to avoid any outbreak of this infection in new entrants there is urgent need for proper sanitation [29,30]. Traveler's account for 10-13% of the acute and fulminant hepatitis A in this study, similar to the earlier reports which estimate an annual infection rate of 3.5-7.2 per 100 individuals [18,31].…”
Section: Discussionsupporting
confidence: 86%
“…The present study showed that one third of hepatitis A patients had insufficient sanitation or poor hygienic conditions with overcrowded population. As reported earlier, low standards of sanitation promote transmission of the virus, therefore, to avoid any outbreak of this infection in new entrants there is urgent need for proper sanitation [29,30]. Traveler's account for 10-13% of the acute and fulminant hepatitis A in this study, similar to the earlier reports which estimate an annual infection rate of 3.5-7.2 per 100 individuals [18,31].…”
Section: Discussionsupporting
confidence: 86%
“…Family size was not significantly associated with income or education, making it difficult to explain as a proxy for improved socioeconomic status. This association is opposite from the increased risk shown for HAV infection in larger families in India [60].…”
Section: Discussioncontrasting
confidence: 63%
“…Seroprevalence reports vary dramatically from country to country and study to study with some studies reporting overall declines in seroprevalence over time, while other yield continued high levels of seroprevalence [ 80 , 82 , 83 ]. Prevalence of anti-HEV IgG tends to increase with age, especially in men [ 80 , 84 , 85 , 86 , 87 ]. Humans and other animals excrete a considerable amount of virus early in the acute phase of HEV infection and likely contribute to maintain the cycle of endemicity [ 76 ].…”
Section: Epidemiology Of Hev Infectionmentioning
confidence: 99%